Occurrence of High Microsatellite-Instability/Mismatch Repair Deficiency in Nearly 2,000 Human Adenocarcinomas of the Gastrointestinal Tract, Pancreas, and Bile Ducts: A Study From a Large German Comprehensive Cancer Center - Quaas, Alexander; Rehkaemper, Jan; Rueschoff, Josef; Pamuk, Aylin; Zander, Thomas; Hillmer, Axel; Siemanowski, Janna; Wittig, Jana; Buettner, Reinhard; Plum, Patrick; Popp, Felix; Gebauer, Florian; et al. (Frontiers in Oncology, 2021)
Introduction Knowledge of the high microsatellite-instability (MSI-H)/mismatch repair deficiency (MMRd) status is of increasing interest for personalized neoadjuvant or adjuvant therapy planning. Only a few studies are available on MSI-H distribution in the Northern European Caucasian patient population. In this study, we focused on a large cohort of tumors of the upper gastrointestinal tract. Materials and Methods Surgical material from a total of 1965 patients was analyzed for MSI-H/MMRd status (including 1267 carcinomas of the esophagus or stomach). All tumors were analyzed with an internationally recommended immunohistochemical panel consisting of four antibodies (MLH1, MSH2, PMS2, and MSH6). The results were molecularly objectified. Results Adenocarcinomas with MSI-H/MMRd were detected with the following distribution: esophagus (1.4%), stomach (8.3%), small intestine (18.2%), large intestine (8.5%), intrahepatic bile ducts (1.9%), and pancreas (0%). In case of gastric tumors with MSI-H/ MMRd, neoadjuvant therapy did not influence the prognosis of patients (p = 0.94). Within all tumor entities with MSI-H/MMRd, patients with an UICC stage 4 were also represented. In this advanced stage, 11.7% of patients with MSS tumors were diagnosed compared to 0.5% of patients with MSI-H tumors relative to the entire tumor collective. Discussion In this study, the proportion of MSI-H/MMRd tumors in the stomach is smaller than would have been expected in knowledge of the data published by TCGA or AGRC. Negative prognostic effects regarding MSI-H status and neoadjuvant therapy as described by the MAGIC study group were not seen in our cohort. The extent to which the MSI-H/MMRd status should be known for neoadjuvant therapy planning must be clarified in prospective studies in the future. At present, there is no convincing data to dispense the neoadjuvant therapy for gastric carcinoma. Due to the very convincing, positive data regarding the response rates of MSI-H tumors to treatment with PD1/PD-L1 inhibitors, every metastatic carcinoma of the gastrointestinal tract should be tested for its MSI-H status.